Measuring the unknown: the concept of intelligence in the Brazilian educational context in the 1920s and 1930s (Memorandum: Memory and History in Psychology, 2019)
The intelligence tests developed at the beginning of the XX century played a decisive role in the reorganization process of Brazilian school education. The Belo Horizonte Teachers College had the function of training teachers for modern and scientific practices. The aim of this research was to analyze the concepts of intelligence that circulated in the state of Minas Gerais in the 1920s and 1930s, under the influence of the teaching of tests to the students from the Teachers College. Methodologically, we started from the concept of reception/circulation, which refers to the process of appropriation of instruments, ideas and concepts produced in other places. As a result, we were able to demonstrate that the practical use of the tests had supremacy over the theoretical debate about the notion of intelligence. We concluded that the experience of the Belo Horizonte Teachers College focused on the pragmatic use of tests, in detriment of the theoretical discussion about intelligence.